The impact of gender segregation on male-female wage differentials: evidence from matched employer-employee data for Spain - Catalina Amuedo-Dorantes; Sara de la Rica (Institute for the Study of Labor (IZA), 2005)
This paper presents new evidence on the role of gender segregation within industry, occupation, establishment, and occupation-establishment cells in explaining gender wage differentials of full-time salaried workers in Spain during 1995 and 2002. Using data from the Spanish Wage Structure Surveys, we find that the raw gender wage gap decreased from 0.26 to 0.22 over the course of seven years. However, even after accounting for workers' human capital, job characteristics, and female segregation into lower-paying industries, occupations, establishments, and occupations within establishments, women still earned approximately 13 percent and 16 percent less than similar male counterparts as of 1995 and 2002, respectively. Most of the gender wage gap is attributable to workers' sex. Yet, female segregation into lower-paying occupations within establishments, establishments and industries accounted for a sizable and growing fraction of the female-male wage differential.
Keywords: J16; J7; 330; gender wage differentials; female segregation; matched employer-employee data